1976
DOI: 10.1001/archderm.112.9.1256
|View full text |Cite
|
Sign up to set email alerts
|

Noninflammatory destruction of actinic keratoses by fluorouracil

Abstract: Sequential topical application of fluorouracil and 0.5% triamcinolone acetonide cream is as effective in the treatment of actinic keratoses as fluorouracil alone, but the combination obviates the unpleasent irritation caused by fluorouracil. Diluted (0.1%) triamcinolone acetonide cream preparations are ineffective in the suppression of the associated inflammation. There is no detectable difference in the number of new actinic keratoses between the combination therapy and fluorouracil alone. These findings demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Photodamage severity was determined using the validated Griffiths scale (0-8). 30 The patients' clinical features were compared with 5 standardized photographs showing no damage (0) to severe damage (8). Exclusion criteria included a history of porphyria or photosensitivity, hyperkeratotic AKs, active infectious disease, pregnancy or lactation, or use of photosensitizing drugs (eg, tetracycline and retinoids).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodamage severity was determined using the validated Griffiths scale (0-8). 30 The patients' clinical features were compared with 5 standardized photographs showing no damage (0) to severe damage (8). Exclusion criteria included a history of porphyria or photosensitivity, hyperkeratotic AKs, active infectious disease, pregnancy or lactation, or use of photosensitizing drugs (eg, tetracycline and retinoids).…”
Section: Experimental Designmentioning
confidence: 99%
“…Patients with relatively few AKs are most often treated with local liquid nitrogen cryotherapy, 5 a treatment modality associated with mild to moderate discomfort, and monitored at intervals of several months to a year for new and recurrent lesions that are then also treated. 7 Patients with extensive AKs are usually offered treatment with topical fluorouracil 8,9 or, more recently, diclofenac, [10][11][12] cancer chemotherapeutic agents applied twice daily for several weeks to broad areas in an effort to destroy "subclinical" as well as clinically apparent AKs. 13 However, such treatment is invariably associated with pain, pruritus, and burning, and patient compliance is poor.…”
mentioning
confidence: 99%
“…10,11 Clinical trials have repeatedly found topical fluorouracil to be effective for the treatment of AK lesions when applied in concentrations of 0.5%, 1%, and 5%. [12][13][14][15][16] The long-term outcomes of cryosurgery and the effect of a regimen using topical fluorouracil before cryosurgery have not been evaluated in randomized or controlled trials. A 1-week course of topical 0.5% fluorouracil is effective and well tolerated in the treatment of AK.…”
mentioning
confidence: 99%
“…Our patient partially responded to topical 5-FU cream and tretinoin 0.1 % cream; the verrucous lesion mostly disappeared. 5-FU is a potent anti-proliferative chemotherapeutic agent which primarily affects cells actively synthesizing DNA (11,12). Topical tretinoin may also be beneficial, because, in addition to its well-known inhibitory effect on keratinocyte differentiation, it enhances percutaneous absorption of chemicals (13).…”
Section: Discussionmentioning
confidence: 99%